STUDENTS' PERSPECTIVES ON ECO-ENZYME-BASED SUSTAINABLE LIFESTYLE INTEGRATION - Henni Fitriani; Nuraini Fatmi; Harizki Ananda Putra (SUJANA: Education and Learning Review, 2024)
This study aims to evaluate the understanding of students of State High School 3 Lhokseumawe about the concept of coenzyme and how they integrate sustainable practices through the Pancasila Student Profile Strengthening Project. The methodology used is a quantitative descriptive survey with a questionnaire that includes various indicators, such as understanding the concept of coenzyme, participation in the project, and motivation to apply coenzyme in daily life. The data obtained were analyzed using descriptive statistical methods. Each question item is analyzed to produce an average score and a percentage representing the respondent's level of understanding, participation, and perception. The average score of each indicator is calculated to determine students' level of understanding, perception, and motivation. The average score is compared with the assessment criteria to interpret the survey results. The results showed that student's level of understanding was relatively high (84%), and their perception of the use of coenzymes was positive (82%). The Pancasila Student Profile Strengthening Project is considered effective in increasing education about organic waste management (86%), but active participation in the project is still moderate (76%). Students' awareness of the importance of reducing organic waste after P5 activities was reflected in the motivation value of 4.0 (80%) and the impact of the Pancasila Student Profile Strengthening Project on environmental awareness (90%). Respondents are also aware of integrating Pancasila Student Profile values in this project (84%). These results indicate that the Pancasila Student Profile Strengthening Project effectively supports understanding and awareness of sustainable lifestyles. This study shows that overall, students have a positive perspective on the integration of sustainable lifestyles through the use of coenzymes.